Pengaruh Pemberian Kompres Hangat Jahe Merah Terhadap Nyeri Pada Pasien Gout Arthritis di Kelurahan Mahawu Manado - Faradilla Mifta Suranata; Rahmat H. Djalil; Ratna Novitasari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Gout Arthritis is a disease characterized by pain that occurs repeatedly caused by deposits of monosodium urate crystals that accumulate in the joints as a result of high levels of uric acid in the blood. One of the complementary therapeutic measures is a warm red ginger compress in gout arthritis patients. The purpose of this research is to determine the Effect of Giving Warm Red Ginger Compresses to Pain in Gout Arthritis Patients in Mahawu Village, Manado. The design of this study used a pre- experimental (one-group, pre-post test design). The sample in this study was 35 respondents taken using a total sampling instrument. The study used observation sheets and SOPs for measurement using the NRS (Numeric Rating Scale). The data were then analyzed using the Wilcoxon statistical test with a significance level of = 0.05. The results of this study indicate that there is an effect of giving red ginger warm compresses to pain in gout arthritis patients with p value = 0.000 <0.05 so Ha is accepted and Ho is rejected. So it can be concluded that there is an effect of giving red ginger warm compresses to reducing pain in gout arthritis patients in Mahawu Village, Manado. The conclusion of the study is that there is an effect of warm red ginger compresses on Gout Arthritis patients in Mahawu Village, Manad.